Comparing species richness and abundance of bumble bees between urban and natural areas using a photographic survey approach - MacLeod, Janelle; Silva-Opps, Marina; Sanchez, Javier (Frontiers in Ecology and Evolution, 2024)
Bumble bees are essential pollinators that provide critical ecosystem services yet, studies are documenting global species declines while recognizing those declines may be understated due to insufficient baseline data. This study investigates bumble bee species richness and abundance across urban and natural sites in Prince Edward Island, Canada, focusing on Charlottetown (urban) and Prince Edward Island National Park (natural). We conducted fieldwork in August and September 2019 using a non-invasive photographic survey technique. We used published keys and sought feedback from citizen science platforms like iNaturalist and Bumble Bee Watch to verify species identification. Our results revealed nine bumble bee species, with Bombus impatiens being the most abundant and Bombus perplexus the rarest. Species richness was higher in natural sites, while urban sites demonstrated moderate levels of bumble bee diversity. Additionally, our findings suggest that sites containing a mix of natural and human-cultivated plant types, predominantly found in our urban study sites, may support higher diversity and evenness levels than those of homogenized plant types (natural or human-cultivated). This research illustrates the practicality of photographic surveys to document the species richness and diversity of bumble bees while avoiding disturbance to populations in urban and natural habitats of Prince Edward Island.